2014
DOI: 10.1016/j.devcel.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Cells from the Immune System Generate Adult-Born Neurons in Crayfish

Abstract: Neurogenesis is an ongoing process in the brains of adult decapod crustaceans. However, the first-generation precursors that produce adult-born neurons, which reside in a neurogenic niche, are not self-renewing in crayfish and must be replenished. The source of these neuronal precursors is unknown. Here, we report that adult-born neurons in crayfish can be derived from hemocytes. Following adoptive transfer of 5-ethynyl-2'-deoxyuridine (EdU)-labeled hemocytes, labeled cells populate the neurogenic niche contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 39 publications
5
108
1
Order By: Relevance
“…Evidence to support this hypothesis is shown in Figure 3, where in situ hybridization for CHF mRNA clearly shows cells with and without CHF expression (a marker for SGCs) (Figure 3). Recent studies have also shown a link between the immune system and adult neurogenesis in crayfish; therefore, cells within the APC and/or HPT likely give rise to neuronal precursors (Beltz et al, 2015(Beltz et al, , 2011Benton et al, 2014). However, to obtain a clear picture of how commitment and differentiation are regulated in this tissue, it is absolutely necessary to identify additional markers for the different stages of development into different mature hemocyte types, as illustrated in Figure 3.…”
Section: Hemocyte Lineages and Releasementioning
confidence: 99%
“…Evidence to support this hypothesis is shown in Figure 3, where in situ hybridization for CHF mRNA clearly shows cells with and without CHF expression (a marker for SGCs) (Figure 3). Recent studies have also shown a link between the immune system and adult neurogenesis in crayfish; therefore, cells within the APC and/or HPT likely give rise to neuronal precursors (Beltz et al, 2015(Beltz et al, , 2011Benton et al, 2014). However, to obtain a clear picture of how commitment and differentiation are regulated in this tissue, it is absolutely necessary to identify additional markers for the different stages of development into different mature hemocyte types, as illustrated in Figure 3.…”
Section: Hemocyte Lineages and Releasementioning
confidence: 99%
“…Moreover, increasing description of the nervous regulation of hematopoietic function, together with the putative importance of the relationship between SVZ vasculature and NSCs, seems to be the dawn of an interpenetration of both systems. Likewise, recent findings demonstrating that crayfish neurons are generated from the immune system is another example of this crisscross (Benton et al, 2014). We therefore suggest that in mammals, the interpenetration of both systems relies, at least partly, on neural crest derivatives present in bone marrow.…”
Section: Discussionmentioning
confidence: 87%
“…However, between days 8 and 14 after injection, BrdU + cells were once again observed in the niche. Adapted from Benton et al [2014].…”
Section: The Innate Immune System Of Crayfishmentioning
confidence: 99%
“…One of these concerns the functional relationships between adult neurogenesis and the immune system. The immune system plays critical roles in combating disease, in neural physiology and development, and in regulating neural stem cell (NSC) niches in both vertebrate and invertebrate species [Perry et al, 1993[Perry et al, , 2010Gonzalez-Perez et al, 2010Paolicelli et al, 2011;Benton et al, 2014]. However, while immunological mechanisms involved in adult neurogenesis are of potential broad importance to our understanding of how the normal brain is maintained throughout life, the contributions of the immune system to adult neurogenesis remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%